2010
DOI: 10.1074/jbc.m110.118471
|View full text |Cite
|
Sign up to set email alerts
|

Serglycin-independent Release of Active Mast Cell Proteases in Response to Toxoplasma gondii Infection

Abstract: Earlier studies identified serglycin proteoglycan and its heparin chains to be important for storage and activity of mast cell proteases. However, the importance of serglycin for secretion and activity of mast cell proteases in response to parasite infection has been poorly investigated. To address this issue, we studied the effects on mast cell proteases in serglycin-deficient and wild type mice after peritoneal infection with the obligate intracellular parasite Toxoplasma gondii. In line with previous result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
(56 reference statements)
2
12
0
Order By: Relevance
“…Although mast cells incubated with non-opsonized tachyzoites did not show any sign of degranulation, in line with previous data 51 , opsonized tachyzoites induced a strong and polarized degranulation. Interestingly, exposure of parasite to mast cell granules upon synaptic contacts was accompanied by its death, which was at least partially dependent of a functional mast cell tryptase.…”
Section: Discussionsupporting
confidence: 92%
“…Although mast cells incubated with non-opsonized tachyzoites did not show any sign of degranulation, in line with previous data 51 , opsonized tachyzoites induced a strong and polarized degranulation. Interestingly, exposure of parasite to mast cell granules upon synaptic contacts was accompanied by its death, which was at least partially dependent of a functional mast cell tryptase.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, several reports show that serglycin (or purified heparin) can enhance the actual activity of the MC proteases, either by promoting protease assembly (Hallgren et al , 2004 ) or by facilitating MC protease-catalyzed cleavage of certain substrates (Pejler and Sadler , 1999 ;. However, the release of MC proteases may occur independently of serglycin proteoglycan, at least during an in vivo response to parasite infection (Sawesi et al , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of MC-deficient Kit W / Kit W-v mice demonstrated that the influx of Ly6G + cells toward the peritoneal cavity was significantly reduced compared to control littermates, indicating that MCs are an important chemokine source driving PMN recruitment to the peritoneal cavity during T. gondii infection (43). In both wild-type and serglycin-deficient mice, intraperitoneal infection with T. gondii resulted in highly increased extracellular levels of glycosaminoglycans, including hyaluronan and chondroitin sulfate A, suggesting that serglycin proteoglycan is dispensable for normal secretion and activity of MC proteases in response to T. gondii infection (81). A murine model showed that infection of T. gondii increased not only the number of MCs at the site of infection but also a noticeable degree of MC degranulation.…”
Section: Mcs In T Gondii Infectionmentioning
confidence: 99%